Facile electrochemical fabrication of Nickel-Coated Polydiphenylamine (Ni/PDPA) nanocomposite material as efficient anode catalyst for direct alcohol fuel cell application. (15th September 2022) - Raveendran, Asha; Chandran, Mijun; Mohammad Wabaidur, Saikh; Ataul Islam, Md; Dhanusuraman, Ragupathy; Ponnusamy, Vinoth Kumar
Graphical abstract: Highlights: Facile electrodeposition of Nickel and Polydiphenylamine on Fluorine tin-doped electrode. Synergistic effect between Nickel and PDPA enhanced methanol and ethanol electrooxidation. Rct value of Ni/PDPA is relatively lower than PDPA alone, indicating lower charge resistance. Enhanced stability of Ni/PDPA compared to PDPA. Ni/PDPA is highly cost-effective compared to platinized electrode material for DAFCs. Abstract: Methanol and ethanol oxidation in fuel cells is considered an alternative effective renewable energy. In this work, we investigated the electrooxidation of methanol and ethanol using a novel nanohybrid material consisting of polydiphenylamine (PDPA) and nickel (Ni) nanoparticles onto fluoride doped tin oxide (FTO) electrode using a facile electrodeposition method. The fabricated electrode was well-characterized using X-ray diffraction, field-emission scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy techniques, and Fourier-transform infrared spectroscopy to confirm Ni/PDPA formation. Electrochemical measurements were carried out in 0.1 M KOH, and Ni/PDPA demonstrated excellent electrocatalytic activity due to synergistic effect owing to relatively lower onset potential by Ni and high conductivity of the conductive polymer. In addition, Ni/PDPA catalysts exhibited high current density, relatively low Rct value, and better stability. Based on the obtained electrochemical results, it is confirmed that Ni/PDPA catalysts synthesized via electrodeposition are time-saving, economically viable, and suitable for fuel cell applications, particularly in direct alcohol fuel cells.